Temptation in Vote-Selling: Evidence from a Field Experiment in the Philippines - Allen Hicken; Stephen G. Leider; Nico Ravanilla; Dean Yang (Center for Economic Studies and ifo Institute (CESifo), 2014)
We test the predictions of a behavioral model of transactional electoral politics in the context of a randomized anti-vote-selling intervention in the Philippines. We model selling one's vote as a temptation good: it creates positive utility for the future self at the moment of voting, but not for past selves who anticipate the vote-sale. We also allow keeping or breaking promises regarding vote-selling to affect utility. Voters who are at least partially sophisticated about their vote-selling temptation can thus use promises not to vote-sell as a commitment device. An invitation to promise not to vote-sell is taken up by a majority of respondents, reduces vote-selling, and has a larger effect in electoral races with smaller vote-buying payments. The more effective promise treatment reduces vote-selling in the smallest-stakes election by 10.9 percentage points. Inviting voters to make another type of promise - to accept vote-buying payments, but to nonetheless vote your conscience - is significantly less effective. The results are consistent with voters being partially (but not fully) sophisticated about their vote-selling temptation.
Keywords: D03; D72; O12; 330; vote-selling; vote-buying; temptation; self-control; commitment; elections; political economy; Philippines